The synthesis and influence of the novel bispyridinium compound LB1 on the effectiveness of the standard antidotal treatment of organophosphorus nerve agent intoxicated mice and some structure-activity considerations - Kassa, Jiri; Ambler, Rachael E; Brown, Lynda J; Cummins, Jaime; Green, A Christopher; Timperley, Christopher M (Chemico-biological interactions, 2025)
The design of MB327, a bispyridinium compound that ameliorates the nicotinic effects of acute organophosphorus nerve agent (NA) intoxication, followed an observation made by the German pharmacologist Klaus Schoene in the 1970s, who noted therapeutic activity in bispyridinium molecules missing the usual oxime group, CHNOH. Some of these compounds protected mice against soman. One structurally related to obidoxime called HY10 had this action. Its oxime moieties were capped by tert-butyl groups: CH=NOtBu. We modified HY10 by changing the bridge between the pyridinium units from a dimethylene ether to a trimethylene group (CH2OCH2 → CH2CH2CH2) and prepared a novel relative of trimedoxime, called LB1, whose synthesis and stereochemistry are described. Unlike obidoxime or trimedoxime, LB1 because of its capped oxime groups, cannot directly reactivate NA inhibited acetylcholinesterase. Its antidotal activity in mice is now reported. The therapeutic efficacy of LB1, atropine alone, atropine with LB1, atropine with an oxime (HI-6, obidoxime or trimedoxime), and atropine with an oxime and LB1, was studied by determining the LD50 values of the NAs soman, sarin, or tabun in mice treated with these compounds or mixtures. LB1 exceeded MB327 in toxicity and its activity was insufficient for a useful addition to the current standard antidotal treatment (protective ratio data are compared to those of MB327). Although this study produced largely negative biological results, the therapeutically beneficial mechanism of the effective bispyridinium non-oxime analogues is unclear, and has been demonstrated only in vivo. The present study points out directions in structural optimisation unlikely to yield the desired therapeutic outcomes and provides a literature review that could promote creative thinking for the design of widely-desirable non-oxime therapeutics for anticholinesterase inhibitors.
Keywords: Cholinesterase Inhibitors; Male; antidota; Soman; Trimedoxime; Structure-Activity Relationship; Nerve Agents; organofosforové sloučeniny; LB1; Oximes; mužské pohlaví; trimedoxim; Bispyridinium; Mechanism; acetylcholinesterasa; soman; Pyridinium Compounds; vztahy mezi strukturou a aktivitou; Antidotes; Animals; pyridinové sloučeniny; atropin; Organophosphorus Compounds; Pyridinecarboxaldoxime; zvířata; myši; nervová bojová látka; oximy; Nerve agent; Mice; Acetylcholinesterase; cholinesterasové inhibitory; Atropine